Asymmetric nexus between economic policy uncertainty, renewable energy technology budgets, and environmental sustainability: Evidence from the United States. (1st September 2021) - Ahmed, Zahoor; Cary, Michael; Shahbaz, Muhammad; Vo, Xuan Vinh
Abstract: Renewable energy is vital to achieve environmental sustainability, improve public health and address global climate change. However, the transition to renewable energy is impossible without massive public renewable energy research and development budgets (RRDD) along with sustained state and federal policies. RRDD in the US showed significant fluctuations over the last three decades and economic policy uncertainty (EPU) was also highly volatile. Based on this backdrop, this study examined the asymmetric impact of RRDD and EPU on CO2 emissions in the US, accounting for structural breaks in data, and controlling for economic growth and FDI. Keeping in view the overwhelming reliance on linear methods in previous studies, both symmetric and asymmetric ARDL approaches are employed for cointegration and long-run results on quarterly data over the period 1985 to 2017. The outcomes from symmetric and asymmetric cointegration tests unfolded only asymmetric cointegration among variables. The long-run findings unveil that a positive change in EPU mitigates emissions but a dominant reduction in CO2 emissions comes from a negative change in EPU. Therefore, it is highly desirable to reduce EPU to achieve a considerable long-term reduction in CO2 emissions. Surprisingly, positive and negative changes in RRDD do not affect CO2 emissions. Hence, the study could not find any significant reduction in CO2 emissions associated with RRDD, implying that renewable energy technology budgets are not sufficient enough to reduce pollutant emissions. The evidence also confirms that the EKC hypothesis is valid in the US considering RRDD, EPU, and FDI in the model. Finally, the study suggests a significant uplift in RRDD and fiscal policies with more subsidies and tax benefits for the growth of renewable energy sector. Also, stability in the environmental policies, regardless of the economic condition, is necessary to achieve long-term environmental benefits. Highlights: Estimated impact of EPU and renewable energy budgets on CO2 emissions. Positive changes in EPU reduce emissions. Negative changes in EPU mitigate emissions with a more pronounced effect. Renewable energy technology investment is not sufficient to influence emissions. EKC hypothesis is valid.